Hypoxia and Complement-and-Coagulation Pathways in the Deceased Organ Donor as the Major Target for Intervention to Improve Renal Allograft Outcome. Issue 6 (June 2015) - Damman, Jeffrey; Bloks, Vincent W.; Daha, Mohamed R.; J. van der Most, Peter; Sanjabi, Bahram; van der Vlies, Pieter; Snieder, Harold; Ploeg, Rutger J.; Krikke, Christina; Leuvenink, Henri G.D.; Seelen, Marc A.
<x xml:space="preserve">Abstract</x> Background In the last few decades, strategies to improve allograft survival after kidney transplantation have been directed to recipient-dependent mechanisms of renal injury. In contrast, no such efforts have been made to optimize organ quality in the donor. Optimizing deceased donor kidney quality opens new possibilities to improve renal allograft outcome. Methods A total of 554 kidney biopsies were taken from donation after brain death (DBD) and donation after cardiac death (DCD) kidneys before donation, after cold ischemia and after reperfusion. Healthy living donor kidney biopsies served as controls. Transcriptomics was performed by whole genome microarray analyses followed by functional pathway analyses. Results Before organ retrieval and before cessation of blood circulation, metabolic pathways related to hypoxia and complement-and-coagulation cascades were the major pathways enhanced in DBD donors. Similar pathways were also enriched in DCD donors after the first warm ischemia time. Shortly after reperfusion of DCD grafts, pathways related to prolonged and worsening deprivation of oxygen were associated with delayed graft function in the recipient. Conclusion In conclusion, this large deceased donor study shows enrichment of hypoxia and complement-and-coagulation pathways already in DBD donors before cessation of blood flow, before organ retrieval. Therefore, future intervention therapies should target hypoxia and complement-and-coagulation cascades in the donor to improve renal allograft outcome in the recipient.